Investigating the Morphometric Characteristics of Male and Female Zell Sheep Skulls for Sexual Dimorphism - Behrokh Marzban Abbasabadi; Omid Hajian; Saber Rahmati (Negah Institute for Scientific Communication, 2020)
Introduction: The present study aimed to evaluate the morphometric differences of the skull in male and female Zell sheep.  Methods: A total of 30 Zell sheep skulls (15 adult males and 15 adult females) were used in this investigation. The skulls were cleaned by boiling maceration, and the mandibles were disarticulated from the temporomandibular. Then, 19 parameters of the skull and 13 parameters on the mandibles were measured using a digital Vernier caliper. The obtained results were analyzed in SPSS by Independent Samples t-test (P<0.05). Results: The distance of lateral alveolar root to mental foramen was significantly higher in male Zell sheep (accuracy rate: 83.33%); however, no statistically significant difference was observed in other cases. Furthermore, the mandible and the skull of Zell sheep were the smallest among the other studied sheep breeds. Conclusion: The distance of lateral alveolar root to mental foramen on mandible can be an appropriate landmark in gender estimation in Zell sheep.